Culture, Art and Film in an African Society: An Evaluation (Nordic Journal of African Studies, 2003)
In this treatise, attention is drawn to the inability of the African filmmakers to adopt and deculturize the film genre – a relatively new literature – to suit African culture. The filmmakers in the Yorùbá community of West Africa are used as the case study.It is observed that there is a sharp contrast between the production of the seasoned filmmakers and the new bunch of filmmakers that can be regarded as "neophytes". While the professional film producers opt for a good production in terms of quality imagination, entertainment, and education, the pseudo-professional filmmakers prefer emotional and sensational films which lack lustre.This study highlights different steps to be taken in production of feature films. These include acculturation of film genre in line with African culture, exploration of African cultured resources, and delineation between technology and arts.Three words which need brief clarity in this paper are Culture, Art and Film. It is imperative to consider these three words within the framework of this paper.